Magnetic Resonance Imaging Lesions in the Central Nervous System of a Dog with Canine Monocytic Ehrlichiosis. (18th January 2012) - Lang, Linda G.; Griffin, John F.; Levine, Jonathan M.; Breitschwerdt, Edward B.
Abstract : A ten-year-old neutered male dog was examined for tetraparesis, vestibular dysfunction, ataxia, and vertebral column hyperesthesia of 10 days duration. On magnetic resonance imaging (MRI), there were multifocal, punctate, T2-hyperintense lesions in the brain and cervical spinal cord and intracranial leptomeningeal contrast enhancement. Cerebrospinal fluid (CSF) analysis revealed a predominantly mononuclear pleocytosis and mildly elevated protein. Ehrlichia canis was diagnosed by serum immunofluorescent antibody (IFA) testing. The dog improved with administration of doxycycline. This report describes MRI central nervous system findings in a dog with ehrlichiosis.